The development of students' cultural awareness through an indonesian cross-cultural counseling - Fadhilla Yusri; Yeni Afrida (Indonesian Institute For Counseling, Education and Therapy, 2020)
This research was conducted to increase the cultural awareness of prospective counselors in the implementation of cross-cultural counseling. The quality of cross-cultural counseling is influenced by the cultural awareness of the counselor and the counselee that get the serves form the counselor. This study aims to reveal the cultural awareness that counselors have in conducting cross-cultural counseling and increase it through three types of treatment: (1) counselors understand the culture of the counselee from experts who have different cultural backgrounds from the counselee to be reached; (2) prospective counselors understand the culture of the counselee from the peers who have different backgrounds from the counselee who wants to be understood; and (3) prospective counselors understand the culture through individuals who were born and raised in the culture of the counselee to be reached. This research was conducted using action research methods. The population in this study were all students of the BK IAIN Bukittinggi study program who took courses in cross-cultural counseling, as many as 110 people. The sampling technique used is an accidental sample of 40 people. The treatment for the development of cultural awareness was carried out in a classical format through three cycles. Analysis of the acquisition data in each cycle proves that cultural awareness can be developed through the treatments given.